Removal of arsenic from aqueous solution using a surface-functionalized magnetic biochar derived from Chlorella - Muhammad Irfan; Israr Masood ul Hasan; Muhammad Jafir; Chang Li; Jie Hu; Muhammad Moeen ud din; Khalid Hussain; Yixing Zhu; Liugen Zheng (Marine Pollution Bulletin, 2026)

Machine learning-assisted meta-analysis reveals melatonin crosstalk regulating plant growth plasticity under heavy metal stress - Muhammad Moeen-ud-din; Muhammad Azher Hassan; Ambreen Ahmad; Liu Xianhua; Muhammad Ishfaq; Muhammad Irfan; Yujiang Li; Liu Yang; Liu Chunguang (Plant Cell Reports, 2026)

Fate and transport of viruses in the subsurface environment: A systematic review of pollution pathways in saturated and unsaturated porous media - Muhammad Yousuf Jat Baloch; Purnima Baidya; Manita Aryal; Muhammad Moeen-ud-din; Liu Yang; Javed Iqbal; Mariusz Ptak; Predrag llić; Chunguang Liu (Environmental Research, 2026)

Study on coal-based solid state reduction of Panzhihua ilmenite - Wu Pengsen; He Benliu; Chen Jianli; Zhang Yurong; Du Jingwei; Muhammad Moeen; Gong Junju; Guo Yufeng; Qiu Guanzhou (Minerals Engineering, 2025)

Zero-carbon solution: Microalgae as a low-cost feedstock for fuel production and carbon sequestration - Moeen Ali Rashad; Farrukh Jamil; Murid Hussain; Abrar Inayat; Parveen Akhter; Muhammad Haris Hamayun; Ali Ahsan; Young-Kwon Park (Critical Reviews in Environmental Science and Technology, 2025)

Enhanced electrocatalytic OER performance of Ba/CS-CoFe2O4 ternary heterostructure catalyst: Experimental and theoretical insights - Qirat Yameen; Muhammad Ikram; Sawaira Moeen; Muhammad Imran; Anwar Ul-Hamid; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Chemosphere, 2025)

Synergistic performance of silver/polyacrylic acid doped ZrO2 nanostructures for dye degradation and bactericidal behavior with molecular docking analysis - Muhammad Ikram; Alvina Rafiq Butt; Sidra Bano; Sadia Naz; Sawaira Moeen; Anwar Ul-Hamid; Ali Haider; Amel Ayari-Akkari (Environment, Development and Sustainability, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Machine learning assisted improved desalination pilot system design and experimentation for the circular economy - Waqar Muhammad Ashraf; Muhammad Ahmad Jamil; Ghulam Moeen Uddin; Bashar Shboul; Kashif Ishfaq; Kim Choon Ng; Mike Dixon; Ben Bin Xu; Muhammad Wakil Shahzad (Journal of Water Process Engineering, 2024)

Polyvinylpyrrolidone and chitosan-coated magnetite (Fe3O4) nanoparticles for catalytic and antimicrobial activity with molecular docking analysis - Ayesha; Muhammad Imran; Ali Haider; Iram Shahzadi; Sawaira Moeen; Anwar Ul-Hamid; Walid Nabgan; Anum Shahzadi; Thamraa Alshahrani; Muhammad Ikram (Journal of Environmental Chemical Engineering, 2023)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Soil salinity detection and monitoring using Landsat data: a case study from Kot Addu, Pakistan - Moeen Ijaz; Hamaad Raza Ahmad; Sadia Bibi; Muhammad Ashar Ayub; Shoaib Khalid (Arabian Journal of Geosciences, 2020)

Highly effective removal of Pb2+ in aqueous solution by Na-X zeolite derived from coal gangue - Qilong Ge; Muhammad Moeen; Qi Tian; Jianjie Xu; Kaiqing Feng (Environmental Science and Pollution Research, 2020)